Modelagem, simulação e otimização de secadores convectivos de grãos : determinação da eficiência energética - Johann, Gracielle (2016)
Brazilian agribusiness is one of the most important sources of riches for Brazil, so that the country has a great potential for agricultural production. This, in turn, has increased significantly in recent decades, with a view to inclusion of new production technologies. However, this good productive performance is not accompanied by improvements in post-harvest activities, such as drying, processing, and especially in grain storage. The function of the storage of agricultural products is to ensure the continuous supply of this production in the consumer centers. Thus, the practice of storage and the associated operations, such as cleaning, drying and prophylactic treatments of grains, are part of a strategic planning context, essential for ensuring social and economic stability of any country. Theoretical analysis and modeling grain dryers activities are complex due to the number of factors involved. Obtaining phenomenological models that describe the drying process is of great interest, since they can be used to predict the drying time, when it is carried out at different processing conditions. Since the evaluation of the energy consumption in drying, objective look into the drying conditions that lead to lower energy consumption, where for maintaining the quality of the final product and the lowest processing cost. Thus, this thesis proposes the numerical study of grain drying processes of grapes, Cabernet Sauvignon, and crambe, including modeling, simulation and optimization of dryers in forced convection. It was studied numerically the thin layer drying of grape grains, with distributed parameters, and tested two drying rates. For the employment of the first drying rate, the coefficients effective mass diffusivity and drying constant were estimated. Since, for the second drying rate were adjusted values of the effective mass diffusivity coefficient and the convective mass transfer coefficient. Finally, we tested the equilibrium boundary condition on the surface of the grains. The model that best suited to the experimental data was one in which were estimated the coefficient of effective mass diffusivity and the mass convective transfer coefficient. With these values, it was proved the equivalence of the results obtained using the model of distributed parameters and the concentrated parameters. To this end, it was employed the values of effective mass diffusivity and convective mass transfer coefficient, obtained in thin layer drying study of grape grain with distributed parameters, in the deep bed and lumped parameters model, with double resistance to mass transfer. Energy optimization of the grape and crambe grains drying process in fixed bed, with and without recirculation of exhaust air of the convective dryer, was studied. The behavior of the energy efficiency, defined as the ratio between the amount of energy used in the removal of moisture, to the energy required to heat the drying air, from ambient to the dryer operating temperature, was similar for both grains. The simulations were conducted until the bed of grains reached 13% of average humidity, and set restrictions on the process was 50°C≤TGfeed≤80 °C, 1 m/s≤v≤5 m/s, 0%≤q≤100%. The increased energy efficiency, disregarding the recycling of the drying air, was obtained at 50 °C and 1 m/s. These were milder drying conditions imposed by the set of constraints considered. For the grape grains, maximum efficiency was 2,27% and for the crambe grain 3,06%. The specific energy consumption was lower as was the lower the air flow in the dryer. In the case of grape grains, energy efficiency, generated by reusing the exhaust air was 12,07% and crambe grain 13,26%, both for the dryer operating at 80 °C and 1 m/s, and 99 and 97% recirculation ratio, respectively. Thus, it was concluded that the use of lower drying air flow are recommended for convective drying of grains both in conventional dryers, as those operated with recirculation of the bed air outlet. Since also for both grains, when the dryer was operated conventionally without exhaust air recycling, greater efficiencies have been achieved at lower temperatures. However, when the device was provided with recirculation of exhaust air, the higher the operating temperature of the process, the higher the efficiency.